ANALYSIS OF THE IMPLEMENTATION OF BUSINESS EDUCATION AT AS-SA’ADAH VOCATIONAL SCHOOL EAST JAKARTA - Solehudin, Rd. Heri; Gunawan, Rudy; Widyanti, Maya; Septiana, Kurnia; Andrikas, Yuliarni; Kurniawati, Herni; Artha, Fuad Dwi (Sosiohumaniora, 2024)
This research aims to analyze the implementation of business education at the As-Sa’adah Vocational School, East Jakarta. Business education at this school is the main focus to understand how the material is taught, the teaching methods used, and its impact on students’ interest and involvement in the world of business carried out by the As-Sa’adah Vocational School. The research method used is qualitative research with a case study approach. Data collection was carried out through interviews with students in grades X, XI, and XII and alumni of As-Sa’adah Vocational High School, East Jakarta, selected randomly with 10 individuals from each cohort. The results show that entrepreneurship education at As-Sa’adah Vocational High School provides positive contributions and can cultivate entrepreneurial tendencies among students, especially after graduating from As-Sa’adah Vocational High School. The implication of this research is the need for increased support and resources to support the effective implementation of business education at As-Sa’adah Vocational High School.